A real time approach to user interest classification using DPI - Kang CHEN; Huazheng FU; Chong CHEN; Yuyi ZHANG; Yu WEI (Dianxin kexue)
In recent years, with the rapid development of internet, telecom operators can gather more and more DPI data. How to mine and classify huge amounts of DPI data in real time is the key point. A DPI data classification method was presented, which combined the URL classification model based on mixed n-gram features and the Doc2Vec based text classification algorithm. The DPI data classification speed and classification accuracy were greatly improved, and good support for precise marketing was provided.